Edukasi Kepatuhan Minum Obat melalui Prinsip Tepat Waktu dan Cara pada Remaja Di SMPN 40 Samarinda - Sukmawaty Sukmawaty; Tri Mei Wahyuni Jumiati; Rindi Ardila; Gayuk Kalih Prasesti (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Medication adherence is an important factor in achieving successful therapeutic outcomes. However, many adolescents still lack adequate understanding regarding proper medication use, particularly the principles of correct timing and correct administration. This community service activity aimed to improve adolescents’ knowledge regarding medication adherence through health education at SMP Negeri 40 Samarinda. The method employed was community education through counseling sessions using PowerPoint presentations and leaflets accompanied by pre-test and post-test assessments. The activity involved 28 junior high school students. The results demonstrated an increase in participants’ knowledge following the educational intervention. The average percentage of correct answers increased from 92% in the pre-test to 99% in the post-test. Improvements were also observed in understanding medication intervals and the proper use of measuring devices for syrup medications. This educational activity proved effective in improving adolescents’ knowledge and understanding of medication adherence and may support rational and safe medication use.